Digital Transformation Of Subak Management In Bali Through GIS Implementation - Achmadi, Shilta Inda Qurroti A'yun; Basco, Anjela Faye M.; Sudana, Oka; Rusjayanthi, Ni Kadek Dwi (Lontar Komputer : Jurnal Ilmiah Teknologi Informasi; Vol 14 No 2 (2023): Vol. 14, No. 2 August 2023DO - 10.24843/LKJITI.2023.v14.i02.p03, 2023)
Subak is a customary law society with socio-agrarian-religious characteristics, consisting of a group of farmers who manage the irrigation of rice fields or paddies. The agricultural irrigation system in Bali or Subak was officially recognized as one of the world's cultural heritages in 2012 by UNESCO. Many S ubak data still rely on traditional recording systems, making it crucial to have a digital transformation using an information system platform capable of collecting data on S ubak and providing related information about S ubak in the Bali Province. To address this problem, a mobile-based Geographic Information System (GIS) that encompasses information about Subak is developed. The data collection method used in this research includes literature studies and questionnaires. The result obtained from this research is an Android mobile application tested using Black Box Testing. All tests were successfully met according to the testing criteria that have been established.